Surface roughness and preload loss of implant-supported screw retained three-unit framework fabricated by different techniques - Alsaif, Rawan; Vohra, Fahim; Albaijan, Refal; Alsayed, Hussain; Altuwaijri, Shahad; Alrabiah, Mohammed (Frontiers in Materials, 2026)
AimThis study evaluated the effects of selective laser melting (SLM), milling, and casting fabrication techniques on surface roughness and screw preload loss of three-unit screw-retained implant-supported Cobalt-Chromium (Co-Cr) frameworks.MethodsTen frame-works were fabricated by each fabrication method (n = 10), and the surface roughness (Ra) was measured using a 3D optical profilometer. The frameworks were torqued to 30 Ncm, retightened after 15 minutes, and subjected to 500,000 cycles in a dual-axis chewing simulator. Pre- and post-load reverse torque values (RTV) were recorded for molar and premolar, and the reverse torque difference (RTD) was calculated. Data were analyzed using ANOVA and Tukey-Kramer tests (α = 0.01). Correlation analyses were performed to determine any relation between surface roughness and preload (RTV and RTD) across all groups.ResultsSignificant differences were found in surface roughness and preload loss among groups (p < 0.01). In molars, the milled group showed the lowest Ra (0.30 µm) and highest post-load RTV (25.2 Ncm), followed by the SLM group (1.73 µm, 20.2 Ncm) and cast group (1.65 µm, 16.9 Ncm). In premolars, the milled group again showed the lowest Ra (0.24 µm) and highest RTV (25.2 Ncm), followed by the SLM group (1.66 µm, 19.4 Ncm) and the cast group (2.57 µm, 17.4 Ncm). There was no significant correlation between roughness and preload loss.ConclusionDifferent manufacturing technique significantly affects surface topography and screw preload. Milled frameworks showed the least surface roughness and the most torque stability.